The Effect of Ethical Climate on Employee Performance Mediated by Communication at PT. Pos Indonesia Malang - Iqbal Robbie; Daffa Aryadana Tanaya; Mursidi (Manajemen Bisnis, 2022)
This study aims to examine the effect of ethical climate on employee performance mediated by communication. This research was conducted at PT. Pos Indonesia Malang Branch. The sampling technique used was total sampling with a sample size of 67 employees of PT. Pos Indonesia Malang Branch. Using a questionnaire as a data collection technique. The data analysis technique used Partial Least Square (PLS). The results of the study conclude that there is a significant influence between ethical climate on employee performance. Ethical climate has a significant effect on communication. Communication has a significant effect on employee performance. Communication mediates the ethical climate on employee performance.